The clinical manifestation and diagnostic features of Kawasaki-like phenotypes in pediatric multisystem inflammatory syndrome: a comparative retrospective study in Ukraine - Bodnarchuk-Sokhatska, Nataliia; Pavlyshyn, Halyna; Kozak, Kateryna; Avramenko, Iryna (Frontiers in Pediatrics, 2025)
BackgroundThe clinical overlap syndrome between multisystem inflammatory syndrome in children (MIS-C) and Kawasaki disease (KD), particularly in the context of SARS-CoV-2 infection, presents diagnostic challenges. The presence of both complete and incomplete Kawasaki-like phenotypes (KLP) further complicates differentiation. This study aimed to analyze Kawasaki-like phenotype of MIS-C, its clinical features, and improve diagnostic accuracy, patient outcomes.MethodsA retrospective cohort study was conducted on 48 pediatric patients diagnosed with MIS-С between 2020 and 2022. All cases met the MIS-C diagnostic criteria established by the Council of State and Territorial Epidemiologists (2022) and were classified according to the American Heart Association Kawasaki disease criteria (2017). Patients were grouped as non–Kawasaki-like or Kawasaki-like MIS-C phenotypes, with the latter subdivided into complete and incomplete subtypes. Clinical and echocardiographic features were compared using appropriate statistical methods.ResultsAmong the 48 MIS-C cases analyzed, 22 patients (46%) met the Kawasaki disease criteria, equally divided between complete and incomplete Kawasaki-like phenotypes. btion was longest in the complete phenotype (9.7 days) and shortest in the incomplete phenotype (5.5 days). Patients with neurological involvement experienced longer febrile periods (8.3 vs. 5.4 days). All 100% patients with the complete phenotype exhibited neurological symptoms vs. 46% of incomplete cases. Half of the Kawasaki-like phenotype patients demonstrated echocardiographic abnormalities vs. 15% of non–Kawasaki-like (NKL); highest in the incomplete phenotype (91%) compared to 15% in non–Kawasaki-like and 9% in complete KLP. The highest incidence of coronary dilatation was recorded in the incomplete phenotype (73%) vs. 9% in the complete and 15% in the non–Kawasaki-like MIS-C.DiscussionKawasaki-like MIS-C phenotypes display distinct clinical and cardiovascular profiles. Accurate phenotypic identification is crucial for risk stratification and optimizing patient management. Further research is necessary to refine classification criteria and establish effective long-term monitoring strategies for affected children.